Implementasi Program Keluarga Harapan (PKH) di Kelurahan Kampung Seraya Kecamatan Batu Ampar Kota Batam - Annisya, Ni Made Oveta; Novira, Alikha (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2023)
Program Keluarga Harapan (PKH) is a program organized by the Ministry of Social Affairs to provide conditional social assistance to the community, especially underprivileged families or poor families. The research was conducted to describe the implementation of the PKH in Kampung Seraya Village. The selection of research locations took into account the number of PKH Beneficiary Families and the number of independent graduates in each village of Batu Ampar District. The data collection process was carried out by interviewing informants, observation, and document studies. Another goal was to find out the driving and inhibiting factors of program implementation, as well as formulating a strategy to improve PKH implementation. The result was implementation of PKH in Kampung Seraya have been running but had several deficiencies, namely there was still a discrepancy in the identity of PKH Beneficiary Families recorded in the DTKS, the Population and Civil Registration Agency, and channeling banks, which affected the distribution of aid funds. There were also several driving and inhibiting factors that influence the implementation of PKH. Author recommends that government can develop and improve the strengths and opportunities as it is explained in the research. In addition, the author also designed a strategy model for updating PKH Beneficiary Family data to minimize identity discrepancies.